Opposite Responses of Interferon and Proinflammatory Cytokines Induced by Human Metapneumovirus and Respiratory Syncytial Virus in Macrophages - Iván Martínez-Espinoza; Antonieta Guerrero-Plata (Pathogens)
Macrophages are a principal pulmonary source of type I and III interferons (IFNs), initiating and coordinating the early antiviral response to respiratory viral infections. Yet the contribution of macrophage-derived IFNs to host defense during human metapneumovirus (HMPV) infection remains poorly defined. Here, we use human primary monocyte-derived macrophages (MDMs) and THP-1-derived macrophages to analyze the IFN responses induced by HMPV compared to its closely related human pneumovirus, respiratory syncytial virus (RSV). We show that HMPV induced a robust response of type I and type III IFNs and ISGs, whereas RSV elicited only a modest, delayed IFN response despite strong IRF activation; instead, RSV preferentially activates NF-κB and exhibits a pronounced proinflammatory cytokine output. Our results highlight the role of macrophages as key modulators of the IFN and proinflammatory responses during HMPV and RSV infection.